Implementation of environmental care character for elementary school students through verticultural culture techniques - Ika Afifah Nugraheni (Peneliti Teknologi Teknik Indonesia, 2021)
The limited area of planting land requires the agricultural system to increasingly utilize a minimalist space in order to produce products that the community wants. This can be done with vertical farming cultivation techniques. This system is suitable to be applied in limited land or in densely populated settlements. One of them is in SD Muhammadiyah Wirobrajan 3 which has limited land. The target of this community service program is 4th grade students of SD Muhammadiyah Wirobrajan 3, Yogyakarta. The implementation activities of this service can be divided into three stages, namely the counseling stage on the introduction of verticulture cultivation techniques to participants, the demonstration stage in the form of vegetable crop cultivation training, and the monitoring stage which is carried out two weeks after the implementation of the service. The vertical rack used is in the form of a vertical paralon pipe rack. Vegetable seeds planted are chicory seeds, spinach, caisim and lettuce. While the planting media used is a mixture of garden soil, compost, husk charcoal, dolomite and NPK fertilizer which is mixed homogeneously so that it is ready for use. At the age of two weeks after planting, the seeds planted on the vertical paralon have begun to appear, indicating plant growth. The introduction of a vertical farming system to students in addition to having a direct impact on the greening of the school environment can also be a form of learning facilities in schools to love the environment more.